Spinal anesthesia for endoscopic submucosal dissection of large rectosigmoid lesions: Feasibility study - Bonura, Giuliano Francesco; Biancheri, Paolo; Rainer, Joachim; Soriani, Paola; Rodriguez de Santiago, Enrique; Parrella, Arianna; Campioli, Alice; Guerra, Emmanuele; Gualdi, Eugenia; Pignatti, Alessandro; Manno, Mauro (Endoscopy International Open, 2024)
Background and study aims Colorectal endoscopic submucosal dissection (ESD) is often challenging and time-consuming. Prolonged sedation and general anesthesia are associated with a relevant risk of anesthesia-related adverse events (ARAEs), especially in elderly and frail patients. Spinal anesthesia (SA), a simple technique providing analgesia and motor block without systemic drug administration, has never been described in gastrointestinal endoscopy. We assessed the feasibility of SA in colorectal lesion ESD.Patients and methods We retrospectively collected data on all consecutive patients who underwent ESD for colorectal laterally spreading tumors (LSTs) under SA in our center during the last 3 years. We evaluated the rates of technical success, i.e. ESD completion under SA without need of conversion to deep sedation or general anesthesia, and ARAEs after SA.Results ESD under SA was performed on 20 rectosigmoid LSTs ≥ 35 mm. Technical success was achieved in 95.0% of cases (19/20), while one patient (5.0%) required conversion to deep sedation. Two patients (10.0%) experienced acute urinary retention that was successfully treated with temporary catheterization.Conclusions Our initial experience suggests that SA for ESD of large rectosigmoid LSTs is feasible, and it may prove to be a valuable option, especially for elderly and frail patients.
Keywords: Quality and logistical aspects; Sedation and monitoring; Endoscopy Lower GI Tract; Polyps / adenomas / ...; Endoscopic resection (polypectomy, ESD, EMRc, ...)